Bioinspired nucleic acid structures for immune modulation. (October 2019) - Louttit, Cameron; Park, Kyung Soo; Moon, James J.
Abstract: Nucleic acids have both extensive physiological function and structural potential, rendering them quintessential engineering biomaterials. As carriers of precisely-tunable genetic information, both DNA and RNA can be synthetically generated to form a myriad of structures and to transmit specific genetic code. Importantly, recent studies have shown that DNA and RNA, both in their native and engineered forms, can function as potent regulators of innate immunity, capable of initiating and modulating immune responses. In this review, we highlight recent advances in biomaterials inspired by the various interactions of nucleic acids and the immune system. We discuss key advances in self-assembled structures based on exogenous nucleic acids and engineering approaches to apply endogenous nucleic acids as found in immunogenic cell death and extracellular traps. In addition, we discuss new strategies to control dinucleotide signaling and provide recent examples of biomaterials designed for cancer immunotherapy with STING agonists.